2013
DOI: 10.1350/ijps.2013.15.3.311
|View full text |Cite
|
Sign up to set email alerts
|

The Enhanced Cognitive Interview: Towards a Better Use and Understanding of This Procedure

Abstract: In 2012, he obtained his masters degree in psychology. His major research topic is investigative interviewing. He has attended and published several papers and posters at scientific conference proceedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 33 publications
(20 reference statements)
1
54
0
8
Order By: Relevance
“…Our study does not support this, because even though the ECI participants are providing more details, they are not eliciting a higher proportion of 'uncertainties'. Such results are highly important for ECI usage, because they suggest that more detailed reports, typically achieved when using the ECI, may well be the result of indeed using diversified and effective recall strategies (Fisher & Geiselman, 1992;Paulo et al, 2013).Witnesses could also be withholding 'uncertain' information' at the beginning of the interview, and later choose to reveal it, assuming that, if the interviewer is asking for successive retrieval attempts, he/she expects more information from the witness, regardless of its accuracy. However, our study does not suggest this because pairwise comparisons revealed no differences between interview phases regarding the amount of produced uncertainties, proportion wise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study does not support this, because even though the ECI participants are providing more details, they are not eliciting a higher proportion of 'uncertainties'. Such results are highly important for ECI usage, because they suggest that more detailed reports, typically achieved when using the ECI, may well be the result of indeed using diversified and effective recall strategies (Fisher & Geiselman, 1992;Paulo et al, 2013).Witnesses could also be withholding 'uncertain' information' at the beginning of the interview, and later choose to reveal it, assuming that, if the interviewer is asking for successive retrieval attempts, he/she expects more information from the witness, regardless of its accuracy. However, our study does not suggest this because pairwise comparisons revealed no differences between interview phases regarding the amount of produced uncertainties, proportion wise.…”
Section: Discussionmentioning
confidence: 99%
“…A few years later, this was further developed by COGNITIVE INTERVIEW: MONITORING AND MOTIVATION 3 Fisher and Geiselman (1992) as the Enhanced Cognitive Interview (ECI). Several social and communicative components, such as rapport building, witness-compatible questioning, transferring control of the interview to the witness and mental imagery, crucial for conducting good investigative interviews, were added (see Fisher, 2014, or Paulo, Albuquerque, andBull, 2013, for more information about the ECI mnemonics and components, as well as the theory underlying such procedures [Tulving, 1991;Tulving & Thomson, 1973]). …”
Section: Developed the Cognitive Interview (Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interviewees were asked to sketch the event and then use that drawing to describe what they had experienced. Sketching the crime scene allows witnesses to initiate their own contextual retrieval cues (Paulo, Albuquerque, & Bull, ). The participants made their drawing on an A3‐sized blank sheet of paper.…”
Section: Methodsmentioning
confidence: 99%
“…Atualmente é considerada uma das técnicas mais efi cazes para melhorar o relato de uma testemunha.Vários estudos têm mostrado que esta técnica aumenta a quantidade de informação evocada pelas testemunhas sem comprometer a exatidão (Milne, Sharman, Powell, & Mead, 2013). Esta entrevista mostrou ser efi caz em diferentes países (EUA, Reino Unido, Alemanha ou Brasil), com diferentes tipos de testemunhas (crianças, adultos ou idosos), diferentes tipos de episódios a recordar (e.g., crimes, acidentes ou chamadas telefóni-cas) e diferentes intervalos de tempo entre o episódio a recordar e a sua evocação (desde poucos minutos a vários dias), tanto em laboratório como em estudos de campo (Paulo, Albuquerque, & Bull, 2013). Quando publicada pela primeira vez, a Entrevista Cognitiva incluía quatro fases ou técnicas: restabelecimento do contexto; contar tudo; mudança de ordem; e a mudança de perspectiva (Geiselman et al, 1984).…”
Section: Entrevista Cognitiva Melhoradaunclassified